Interfacial friction enabling ≤ 20 μm thin free-standing lithium strips for lithium metal batteries - Shaozhen Huang; Zhibin Wu; Bernt Johannessen; Kecheng Long; Piao Qing; Pan He; Xiaobo Ji; Weifeng Wei; Yuejiao Chen; Libao Chen (Nature Communications)
Abstract A practical high-specific-energy Li metal battery requires thin (≤20 μm) and free-standing Li metal anodes, but the low melting point and strong diffusion creep of lithium metal impede their scalable processing towards thin-thickness and free-standing architecture. In this paper, thin (5 to 50 μm) and free-standing lithium strips were achieved by mechanical rolling, which is determined by the in situ tribochemical reaction between lithium and zinc dialkyldithiophosphate (ZDDP). A friction-induced organic/inorganic hybrid interface (~450 nm) was formed on Li with an ultra-high hardness (0.84 GPa) and Young’s modulus (25.90 GPa), which not only enables the scalable process mechanics of thin lithium strips but also facilitates dendrite-free lithium metal anodes by inhibiting dendrite growth. The rolled lithium anode exhibits a prolonged cycle lifespan and high-rate cycle stability (in excess of more than 1700 cycles even at 18.0 mA cm−2 and 1.5 mA cm−2 at 25 °C). Meanwhile, the LiFePO4 (with single-sided load 10 mg/cm2) ||Li@ZDDP full cell can last over 350 cycles with a high-capacity retention of 82% after the formation cycles at 5 C (1 C = 170 mA/g) and 25 °C. This work provides a scalable approach concerning tribology design for producing practical thin free-standing lithium metal anodes.